Oesophageal dilatation on high-resolution computed tomography scan of the lungs as a sign of scleroderma. Issue 9 (28th December 2007) - Vonk, M C; van Die, C E; Snoeren, M M; Bhansing, K J; van Riel, P L C M; Fransen, J; van den Hoogen, F H J
Abstract : Background: Systemic sclerosis (SSc) is a generalised autoimmune disease that causes morbidity and reduced life expectancy. Recently, evidence has been accumulating that immunosuppressive treatment in an early stage of the disease could improve survival, enhancing the need for early diagnosis and regular evaluation of organ involvement. Among others, a high-resolution computer tomography (HRCT) scan of the chest is performed for the assessment of pulmonary involvement in SSc. The objective of this study is to evaluate the predictive value of oesophageal dilatation on the HRCT scan for the diagnosis of SSc. Methods: In total, 105 consecutive patients with scleroderma and 107 consecutive controls were included in this study. The first available scan for each patient and control was evaluated in random order and blinded for the diagnosis, by two independent radiologists, for oesophageal dilatation and interstitial lung disease. Results: The positive predictive value of oesophageal dilatation for the diagnosis of SSc was 83%. No significant correlation of oesophageal dilatation and interstitial lung disease was found in the patients with scleroderma or controls. Conclusion: Oesophageal dilatation as visible on an HRCT scan of the chest may alert doctors to look for other signs or symptoms of SSc in these patients, enabling early diagnosis and specific treatment.